Four Seasons in One Day: The Different Shades of Organisational Culture in Higher Education - HEIDRICH, Balázs; CHANDLER, Nick (Management Dynamics in the Knowledge Economy, 2015)
Using a combination of qualitative and quantitative methods, this study seeks to explore the diversity of culture amongst the staff of a business school in Hungary and then examine how this diversity may impact upon the organisation’s orientations towards three aspects of market orientation: interfunctional cooperation; competition and the student orientation. The diversity of culture is found through the identification of five subcultures. These subcultures exhibit signs of both heterogeneity and homogeneity as two pairs of subcultures are divided not by differences in values themselves but by the expressed strength of values. The empirical findings indicate that each subculture varies in perception of the dominant cultures of the organisation and its particular market orientation in relation to culture type. Furthermore, some subcultures perceive themselves as enhancing, when this may not be the case and others perceive themselves as counter cultures. The qualitative study confirms that subcultures have both homogenous and heterogeneous aspects in relation to other subcultures as well as the perceived dominant culture. This greater complexity gives an extension to the existing perspectives taken on organisation culture, although this would need to be confirmed with generalizable research.